ANALISIS PENGGUNAAN DAKWAAN ALTERNATIF SUBSIDAIR OLEH PENUNTUT UMUM DALAM PERKARA PERLINDUNGAN ANAK - afina akmalia; Arsyad Aldyan (Sebelas Maret University, 2023)
This study aims to determine the suitability of the use of alternative subsidiary forms of indictment by public prosecutors in proving child protection cases with the provisions of the KUHAP based on decision Number 13/Pid.Sus.Anak/2020/PN.Kln. This research is included in normative legal research with a case study. Techniques for collecting primary and secondary legal materials are obtained from document studies or literature. Based on this research, it was found that the use of an alternative subsidiary form of indictment by the public prosecutor in proving child protection cases in Decision Number 13/Pid.Sus.Anak/2020/PN.Kln is by the KUHAP. The Public Prosecutor in preparing the indictment has complied with the provisions stipulated in the Attorney General’s Circular Letter Number SE004/J.A/11/1993 concerning Making Indictments. The preparation of this subsidiary alternative indictment has met the formal and material requirements for an indictment as regulated in the provisions of Article 143 Paragraph (2) of the KUHAP. The Public Prosecutor used an alternative subsidiary form of indictment because the Public Prosecutor was unsure which article was most appropriate to apply to the actions he was charged with against the defendant.Keywords: Indictment, Alternative Subsidiary, Public Prosecutor, Child Protection